Hambatan dan Tantangan Implementasi Kurikulum Merdeka di MTS Raudlatul Uluum Aek Nabara Labuhanbatu - Abdul Fattah Nasution (Journal on Education, 2023)
This research was conducted because the government issued new regulations regarding the curriculum, namely the implementation of an independent curriculum which focuses on students' abilities/character. So the researcher is interested in studying the implementation of the independent curriculum at MTs Raudlatul Uluum. This research was conducted at Mts Raudlatul Uluum with a qualitative descriptive type of research using the interview method. The sources of informants in this study were school supervisors, principals, vice principals and teachers. The results of this study describe the obstacles to implementing the curriculum, namely teachers still have experience with low learning independence, limited references, uneven access to learning, time management and so on. While the challenges in the Education unit, namely; (1) teacher readiness (human resources) as the main pillar of the implementation of the independent curriculum; (2) the ability of teachers to support digital-based technology facilities; (3) increasing communication and collaboration networks between education units and stakeholders; and (4) the difficulty in implementing the learning evaluation function as an integral part of learning. Learning assessment is an important component that schools often ignore in achieving curriculum goals.